Book Reviews (The Muslim world, 1998)
Book reviewed in this article: The IsIamic Intellectual Tradition in Persia. Essays by Seyyed Hossein Nasr. Sufism, Mystics and Saints in Modern Egypt. Qur'ān, Liberation and Pluralism: An Islamic Perspective of Interreligious Solidarity Against Oppression. Taqrir al-Jab al-dlniyyah ff mw [The State of Religion in Egypt Report]. Culture et idéologie dans le monde arabe. Preface par Sami Amin. L'Occident dans l'imaginaire arabo-musulman. L'Islam est-il hostile a la la?cité Islamisme. modernisme, liberalisme. Introduction a la critique de la raison arabe. Muslims and Christians: Face to Face. Juifs et musuhans au Maroc: 1859–1948. Islam and Human Ideology.